Chronology of Veterinary Services Delivery, Basic Infrastructure and Educational Institutions in Sudan (Journal of Veterinary Medicine and Animal Production, 2021)
Sudan is one of the countries in Africa, which received veterinary services early of the first decades of nineteenth century. Although a fixed date is not known, but what realized by many experts, those three veterinarians entered the country accompanying colonial military campaign; form the beginning of veterinary services, which were later diversified and known to include clinical services, veterinary extension and animal production. Furthermore, the governing authorities began to think of administrative organo-structures to manage animals and provide actual needs and requirements of veterinary services and animal health. Implementation of PARC ended in upgrading of field veterinary services and hence provoked eradication of Rinderpest and control of other Trans boundary Animal Diseases (TADs) and non-TADs incidences. It is clear that through the significant contributions of the international community, veterinary services were able to achieve much in short period. The achievement also supported by the national governments through provision of counterpart funds equivalent to and sometimes exceeding that provided by donors. The country started earlier in 1974 to develop the disease free zone with other basic infrastructures, which assisted the veterinary services to promote livestock trade. The concept of provision and distribution of mobile units all over the country contributed to the improvement of field veterinary services and consolidated relationship between the veterinary services and other livestock stakeholders including livestock owners and traders. Veterinary services in the country built strong base for legislation in different aspect of service delivery and standards.
Keywords: Chronology; veterinary services; delivery system; colonial period; Infrastructure; educational Institutions